The leadership challenge how to make extraordinary thing happen in organizations - Kouzes, James M. (Jossey-Bass, 2012)
The 25th anniversary edition of the business classic, completely revised and updated. The Leadership Challenge, based on Kouzes and Posner's extensive research, this all-new edition casts their enduring work in context for today's world, proving how leadership is a relationship that must be nurtured and can be learned. Features over 100 all-new case studies and examples, which show The Five Practices of Exemplary Leadership in action around the world. Focuses on toughest organizational challenges leaders face today. Addresses changes in how people work and what people want from their work. It is an indispensable resource for leaders at all levels.